Ghosts over the boiler: voices from Alabama's death row - Owens-Murphy, Katie (Vanderbilt University Press, 2023)
"From a donated typewriter that frequently breaks down, people on Alabama's death row have literally cut and pasted together a newsletter, On Wings of Hope, for the last three decades to educate the public about the death penalty. This newsletter, a labor of love, documents decades of work, wisdom, activism, and lived experience of those who have been executed, or are scheduled to be executed, by the state of Alabama. The writings also chart the changing policy and practice of capital punishment in the state that sentences more people to death per capita than any other in the US. Ghosts Over the Boiler is a curated collection of poetry, visual art, photographs, essays, creative writings, and other archival materials that have emerged from Alabama's death row from the organization Project Hope to Abolish the Death Penalty (PHADP). This group was founded at Holman Correctional Facility and has been operating autonomously since 1989 toward its mission to abolish the death penalty in Alabama and in the nation."--Page 4 of cover